First report of Meloidogyne javanica on Celosia argentea in the Northeast of Brazil - Mayara Castro Assunção; Francisco Jorge Carlos Souza Junior (Universidade Estadual de Alagoas, 2022)
Celosia argentea is a plant well adapted to the conditions of tropical and subtropical climates, being widely used for medicinal purposes and having high economic value for some regions. Infections caused by Meloidogyne spp. stand out as one of the main phytosanitary problems of C. argentea, with this, the work aimed to identify Meloidogyne species associated with Celosia argentea in areas in the municipality of Guaramiranga, CE, Brazil. The collections were made from roots with galls. Subsequently, the species were characterized through the morphology, esterase phenotypes and molecular analysis of the ITS and 28S rDNA regions. Plants of C. argentea were kept under greenhouse conditions, inoculated with the population of M. javanica (Ms01). The control treatment was not inoculated. The inoculated plants showed root gall symptoms, while the non-inoculated plants showed no symptoms. The species M. javanica was identified. This is the first detection of Meloidogyne javanica in Celosia argentea in Northeast Brazil.